Evaluating Risk Factors for Clostridium difficile Infection In Stem Cell Transplant Recipients: A National Study. (23rd March 2017) - Shah, Nishi N.; McClellan, William; Flowers, Christopher R.; Lonial, Sagar; Khoury, Hannah; Waller, Edmund K.; Langston, Amelia; Nooka, Ajay K.
Abstract : OBJECTIVE: Large-scale studies evaluating risk factors for Clostridium difficile infection (CDI), a leading cause of infectious diarrhea among patients undergoing stem cell transplantation (SCT), are lacking. We have evaluated risk factors for CDI among both autologous SCT (auto-SCT), and allogeneic SCT (allo-SCT) recipients using the National Inpatient Sample (NIS) database provided by the Healthcare Cost and Utilization Project (HCUP). METHODS: We used patient data obtained from the NIS database for all adult patients admitted for auto- and allo-SCTs from January 2001 to December 2010. We performed multivariate logistic regression analyses to evaluate risk factors of CDI in auto- and allo-SCT patients. RESULTS: Auto-SCTs constituted 61.5% of all SCTs performed during the study period. Of the 53, 072 auto-SCT patients, 5.8% had CDI, whereas 8.5% of 33, 189 allo-SCT patients had CDI. Univariate analyses identified age, gender, indication for SCT, radiation as part of the conditioning regimen, respiratory failure, septicemia, lengthy hospital stay, and multiple comorbidities as risk factors for CDI in both subsets. On multivariate analyses for auto-SCT, there was significant correlation between age and the indication for transplant ( P =.003), but the indication for either auto- or allo-SCT was not associated with CDI on multivariate analyses. The following factors were found to be associated with CDI: septicemia (auto-SCT odds ratio [OR], =1.64; 95% confidence interval [CI], 1.35–2; and allo-SCT OR, 1.69; 95% CI, 1.36–2.1), male gender (auto-SCT OR, 1.29; 95% CI, 1.09–1.53; and allo-SCT OR, 1.36; 95% CI, 1.18–1.57), lengthy hospital stay (auto-SCT OR, 2.81; 95% CI, 2.29–3.45; and allo-SCT OR, 2.63; 95% CI, 2.15–3.22), and presence of multiple comorbidities (auto-SCT OR, 1.32; 95% CI, 1.11–1.57; and allo-SCT OR, 1.18; 95% CI, 1.0–1.4). CONCLUSIONS: The prevalence of CDI was higher among patients undergoing allo-SCT. CDI was significantly associated with longer hospital stay, septicemia, and male gender for auto- and allo-SCT recipients. While this analysis did not permit us to directly ascribe the associations to be causative for CDI, it identifies the more vulnerable population for CDI and provides a rationale for the development of more effective approaches to preventing CDI. Infect Control Hosp Epidemiol 2017;38:651–657